(untitled) (Nepal Journal of Epidemiology, 2016)
Unfortunately, it is not feasible to prepare an effective vaccine against scrub typhus, because of the extreme antigenic variation seen amongst the strains of O tsutsugamushi. Immunity acquired naturally against one antigenic type may not be protective against another type which might be currently circulating in the locality. This complexity continues and the problem of making an effective vaccine against this disease still persists.